β-Amyloid: The Key Peptide in the Pathogenesis of Alzheimer’s Disease - Sun, Xiaojuan; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Pharmacology, 2015)
The amyloid β peptide (Aβ) is a critical initiator that triggers the progression of Alzheimer’s Disease (AD) via accumulation and aggregation, of which the process may be caused by Aβ overproduction or perturbation clearance. Aβ is generated from amyloid precursor protein (APP) through sequential cleavage of β- and γ-secretases while Aβ removal is dependent on the proteolysis and lysosome degradation system. Here, we overviewed the biogenesis and toxicity of Aβ as well as the regulation of Aβ production and clearance. Moreover, we also summarized the animal models correlated with Aβ that are essential in AD research. In addition, we discussed current immunotherapeutic approaches targeting Aβ to give some clues for exploring the more potentially efficient drugs for treatment of AD.